Physical and mechanical properties of unripe Nipah banana fruit (Musa acuminata balbisiana) - Zainal A'bidin, Farahana Nabilah; Shamsudin, Rosnah; Mohd Basri, Mohd Salahuddin; Mohd Dom, Zanariah (Universiti Putra Malaysia Press, 2019)
This paper describes the properties determined to acquire physical and mechanical properties of unripe Nipah banana. In Malaysia, most of the banana chips processing companies use a variety from Nipah Banana,also known as Musa acuminata balbisiana a triploid hybrid banana cultivar. The physical (diameter, weight and peel thickness on edge and side) and mechanical properties (penetration and compression test) of Nipah Banana variety were determined through five consecutive days to evaluate its behaviour throughout its ripening period. The average diameter is 38.78±5.77 mm x 29.25±4.92 mm. The average thickness of peel at the edge and side are 5.3±0.93 mm and 3.65±1.01 mm respectively. The average weight of the Nipah banana variety is 77.85±28.61 g. Penetration force through 5 ripening days was found to decrease from 7.53N to 6.59 N (top position), 7.59N to 6.40N (middle position) and 8.31N to 6.43N (bottom position). The compressive force decreases through 3 days from 1704 N to 1630 N with the sudden increase in day 4 to 1380 Using the following properties accumulated, the machine components specification can be obtained which are the blade force required to slit the banana peel, the thickness of the blade needed for the slitting of banana peel, the roller force to hold the banana in place and the peeler size.